2016
DOI: 10.1371/journal.pone.0151968
|View full text |Cite
|
Sign up to set email alerts
|

Family of microRNA-146 Regulates RARβ in Papillary Thyroid Carcinoma

Abstract: Retinoic acid is a promising tool in adjuvant cancer therapies, including refractory thyroid cancer, and its biological role is mediated by the retinoic acid receptor beta (RARβ). However, expression of RARβ is lowered in papillary thyroid carcinoma (PTC), contributing to promotion of tumor growth and inefficiency of retinoic acid and radioactive iodine treatment. The causes of aberrant RARB expression are largely unknown. We hypothesized that the culpable mechanisms include the action of microRNAs from the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
(42 reference statements)
2
31
0
1
Order By: Relevance
“…Reduced RARβ and increased activity of ALDH enzyme have been previously associated with increased miR-146b-5p [30] that was also con rmed in the present study. Additionally, miR-378a-5p overexpression in a rat cardiomyocyte study was associated with ALDH2 downregulation therefore downregulation of miR-378a-5p (Figure 2A) in the present work supported upregulation of ALDH2 in our initial array ( Figure 1A) [31].…”
Section: Resultssupporting
confidence: 91%
“…Reduced RARβ and increased activity of ALDH enzyme have been previously associated with increased miR-146b-5p [30] that was also con rmed in the present study. Additionally, miR-378a-5p overexpression in a rat cardiomyocyte study was associated with ALDH2 downregulation therefore downregulation of miR-378a-5p (Figure 2A) in the present work supported upregulation of ALDH2 in our initial array ( Figure 1A) [31].…”
Section: Resultssupporting
confidence: 91%
“…miRNAs are thought to activate the suppress function on the target gene by the complementary pairing between the sequence of target mRNA and the subsequences completely or in part [13]. There are many studies showing that miRNA is the important part of tumorigenesis; it has been demonstrated that many kinds of miRNAs have the function in cancer promotion or cancer suppression [1416]. At present, the studies have proved that miR-940 was significantly downregulated in malignant tumors, such as gastric cancer and prostate cancer, through the regulation of malignant tumor apoptosis and the suppression of malignant tumor migration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, targeting miR-106a with antagomir increases the expression of NIS and TSHR while sensitizing ATC cells to radioiodine treatment (25). Interestingly, miR-146b regulates the expression of RARβ (26) and serum miR-146b levels are also associated with thyroid tumors poor prognosis (27).…”
Section: Microrna and Thyroid Follicular Cell Differentiationmentioning
confidence: 99%